Adverse Effects of Organochlorine Pesticide Residues on Biochemical Parameters and Oxidative Stress in Libyan Agricultural Workers - Alsalhen, Khaled S.; Omar, Omalsaad E. I. (Al-Mukhtar Journal of Sciences, 2022)
Agricultural workers are in danger of being exposed to toxic substances such as pesticides. To estimate the individual danger of handling pesticides, the bio-monitoring of effects on agricultural workers is required. There has been no such research previously conducted among Libyan agricultural workers. This research was designed to study the biochemical parameters impacts of the pesticide contamination among Libyan agricultural workers at Aljebal Alakhtar, Libya. 45 blood samples were taken from male agriculture workers at Aljebal Alakhtar who had been exposed to pesticides in crop fields for a long time, while 25 blood samples were taken from a group of people who had not been exposed to pesticides (control). Kits were used to assess plasma ALT, AST, ALP, GST, SOD, total protein, albumin, globulin, total bilirubin, total cholesterol, triglycerides, HDL-C, LDL-C, VLDL-C, urea, and creatinine. The thiobarbituric acid reactive substances (TBARS) assay was used to evaluate lipid peroxidation in serum. Using a gas chromatography-electron capture detector, the blood samples were tested for organochlorine pesticide residues (GC-ECD). In comparison to controls, workers had significantly higher SOD, GST, ALP, AST, and ALT activities, as well as higher levels of lipid profile, total bilirubin, creatinine, and urea, as well as significantly higher TBARS concentrations. Furthermore, long-term pesticide exposure was also related to reduceing total protein, albumin, and globulin, as well as reduced HDL-C levels. Pesticide exposure seems to influence various biochemical markers in general. These biomarkers appear to be indicative of pesticide-related deleterious effects in agricultural workers, indicating that they should be used for routine monitoring of impacts.